Using Environmentally Friendly Materials to Improve the Properties of the Drilling Fluid - Assi, Amel Habeeb (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
This study presents a significant advancement in addressing the utilization of environmental additives to improve the properties of drilling mud. The current materials added to drilling fluids could cause a harmful effect on the environment and safety of individuals, highlighting the necessity for alternative additives. In this study, the potential use of orange peel powder (OPP) and Sidr leaf powder (SLP) as environmentally friendly additives to drilling fluid is evaluated. Laboratory tests were conducted to identify the impact of OPP and SLP on the drilling fluid properties. Different weights (1-20) % of OPP and SLP were utilized to prepare the drilling fluid. The results demonstrated that both OPP and SLP affected the rheological properties and filtration of the drilling mud. Notably, the density of the drilling fluid decreased significantly with the addition of crushed Sidr. Attributed to the composition of flavonoids and jujubogenin glycoside in the leaves, and citric acid in the orange peel. The specific weight of SLP and OPP (1.5 and 1.7 respectively) is considerably lower than that of bentonite (2.5), leading to a reduction in density. Sider leaves exhibited a high performance compared to orange peel, with the highest value of yield point, 10 min gel, pH observed at 20 gm of addition. The experimental findings demonstrate the impact of both materials, filtration, viscosity, and alkalinity, with Side leaves proving to be more in enhancing drilling fluid properties.